Impact of Renewable Energy Resources on the Turkish Power Market - Gokce, Burak; Kaya, Gizem; Kayalica, M. Ozgur; Kayakutlu, Gulgun (International Journal of Energy Economics and Policy, 2024)
Power plants using the renewable energy resources are the plants with low marginal costs, and that is why they are given the priority in electricity supply. Therefore, they have a negative impact on spot markets, reducing the market price of electricity, known as merit-order effect. However, the subsidization made through feed-in tariff (FIT) scheme puts a burden on the retail electricity costs. This paper tries to explain the net cost impact of FIT portfolio which consists of wind, solar, hydropower, geothermal, and biofuel sources used in electricity supply in Turkey. Turkish electricity market 2014-2020 period hourly data is analyzed using multiple linear regression model. The results show that merit-order effect is lower than the FIT cost, so increases the total retail cost during the studied period. Moreover, it is important to assess the foreign currency-based scheme at the end of its life cycle and see whether lessons learnt are applied for the new local currency scheme. Additionally, the effect of renewable sources on the volatility of electricity prices are examined using financial time series methods with a focus on COVID-19 pandemic. The conclusion is renewables increase uncertainty, but COVID-19 has no impact.